1981
DOI: 10.1002/jcp.1041090317
|View full text |Cite
|
Sign up to set email alerts
|

Effect of H+ on the kinetics of Na+‐dependent amino acid transport in ehrlich ascites tumor cells: Evidence for H+ as an alternative substrate

Abstract: The effects of H+ on the kinetics of alpha-aminoisobutyric acid (AIB) influx in Ehrlich ascites tumor cells have been investigated at different external Na+ concentrations. Elevation of [H+] in the presence of both high (154 mEq/l) and low (10 mEq/l) external Na+ leads to decreases in the maximum influx (Jmax) and increases in the apparent Michaelis-Menten constant (Km) for influx of AIB. In the virtual absence of external Na+ (0.96 +/- 0.04 mEq/l), alterations in [H+] are without measurable effect on AIB flux… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

1983
1983
1988
1988

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…8 and 9). A similar observation has been previously reported (Heinz et al, 1981;Smith & Robinson, 1981a). It is important to note that, although the cells continuously removed H +, pHi did not change.…”
Section: Discussionsupporting
confidence: 78%
“…8 and 9). A similar observation has been previously reported (Heinz et al, 1981;Smith & Robinson, 1981a). It is important to note that, although the cells continuously removed H +, pHi did not change.…”
Section: Discussionsupporting
confidence: 78%
“…This could result in a lower rate of carrier cycling. Such a mechanism has been proposed to account for inhibition of amino acid transport by H' (Smith and Robinson, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…Garcia-Sancho et al (1977), have suggested that a portion of the energy supply for active transport through System A is de-rived from intracellular reducing equivalents. Smith and Robinson (1981) have proposed that, under certain conditions (low "a+],), amino acid transport could be driven by a proton gradient. Recently, Dawson and Smith (1987) reported that the membrane potential and/or a change in the intracellular Na+ activity, as measured by ion-selective microelectrodes, could provide the needed energy to drive amino acid uptake.…”
mentioning
confidence: 99%